PENGEMBANGAN SISTEM INFORMASI KELURAHAN TEGALHARJO KOTA SURAKARTA DENGAN WORDPRESS CONTENT MANAGEMENT SYSTEM - Diva Rahmaningtyas Citra Ayu Pradani; Dzaky Anwar Zein; Zaki Satria Prayoga; Endah Sudarmilah (Inisiasi, 2023)
The government of Surakarta City uses the WordPress CMS platform to share public information. The obstacle faced at this time is the lack of public information disclosure, especially in the Tegalharjo Sub-district. To improve public information accessibility, we conducted a real-life work practice with the goal of helping the government improve how they share and manage public information by adding PPID information to the sub-districts website and performing website maintenance. The methods we used are included, such as needs analysis, planning, preparation, and website maintenance, followed by a performance evaluation stage. The achieved results make it easy for Tegalharjo Sub-district to handle public information and provide the community with easier access to information from PPID of Surakarta City's.